Analisis Efektivitas Beban Kerja Kepala Sekolah Berdasarkan Permendikbud Ristek No 40 Tahun 2021 - Nopriyanti Nopriyanti; Alhadi Yan Putra; Tri Widayatsih (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to describe the effectiveness of the implementation of the principal's workload based on Permendikbud Ristek No. 40 of 2021 at SD Negeri 1 Lebung Batang, Pangkalan Lampam District. Data collection tools used interview methods, documentation, observation and literature review. Data analysis used descriptive qualitative analysis with the stages of data collection, data reduction, data presentation and drawing conclusions. The results of the study stated that the implementation of the principal's workload in carrying out managerial, entrepreneurial and supervisory tasks in PTK based on Permendikbud Ristek No. 40 of 2021 at SD Negeri 1 Lebung Batang which consists of managerial tasks, has been going well. There are several internal obstacles experienced by the principal in carrying out the workload based on Permendikbud Ristek No. 40 of 2021 at SD Negeri 1 Lebung Batang, Pangkalan District, including the lack of working group forums and training for the principal to attend, limited funds received by the school, lack of facilities and infrastructure, lack of teacher professionalism and lack of involvement of stakeholders and parents of students in making the principal's work programs a success. The solutions taken include trying to take part in training, increasing experience and knowledge and carrying out more effective supervision.